Ultra-thin body and thin-BOX SOI CMOS technology analog ﬁgures of merit - Kilchytska, Valeria I.; Mohd Khairuddin, Md Arshad; Makovejev, Sergej; Olsen, Sarah H.; Andrieu, Francois; Poiroux, Thierry; Faynot, Olivier; Raskin, Jean Pierre; Flandre, Denis (Elsevier Ltd., 2013)
Link to publisher's homepage at http://www.elsevier.com/